2008
DOI: 10.1007/s10800-008-9506-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and electrochemical investigation of RuO2–Ta2O5 oxide films prepared by the Pechini–Adams method

Abstract: Preparation methods can profoundly affect the structural and electrochemical properties of electrocatalytic coatings. In this investigation, RuO 2 -Ta 2 O 5 thin films containing between 10 and 90 at.% Ru were prepared by the Pechini-Adams method. These coatings were electrochemically and physically characterized by cyclic voltammetry, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD). The composition and morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 34 publications
(70 reference statements)
0
24
0
1
Order By: Relevance
“…DSA ® -type electrodes are frequently prepared by thermal decomposition of the precursor metal salts dissolved in HCl:H 2 O 1:1 or isopropanol, a method known as standard thermal decomposition [3,[10][11][12][13][14][15][16][17][18]. Another route for the preparation of DSA ® -type electrodes is the thermal decomposition of polymeric precursors (DPP) [19][20][21][22][23][24][25]. It has been shown that DSA ® -type electrodes prepared by the DPP route are more stable and electrocatalytically activity than those obtained by the STD route [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…DSA ® -type electrodes are frequently prepared by thermal decomposition of the precursor metal salts dissolved in HCl:H 2 O 1:1 or isopropanol, a method known as standard thermal decomposition [3,[10][11][12][13][14][15][16][17][18]. Another route for the preparation of DSA ® -type electrodes is the thermal decomposition of polymeric precursors (DPP) [19][20][21][22][23][24][25]. It has been shown that DSA ® -type electrodes prepared by the DPP route are more stable and electrocatalytically activity than those obtained by the STD route [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Another route for the preparation of DSA ® -type electrodes is the thermal decomposition of polymeric precursors (DPP) [19][20][21][22][23][24][25]. It has been shown that DSA ® -type electrodes prepared by the DPP route are more stable and electrocatalytically activity than those obtained by the STD route [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations